2020
DOI: 10.3897/neobiota.58.33118
|View full text |Cite
|
Sign up to set email alerts
|

The potential current distribution of the coypu (Myocastor coypus) in Europe and climate change induced shifts in the near future

Abstract: The coypu (Myocastor coypus) is a semi-aquatic rodent native to South America which has become invasive in Europe and other parts of the world. Although recently listed as species of European Union concern in the EU Invasive Alien Species Regulation, an analysis of the current European occurrence and of its potential current and future distribution was missing yet. We collected 24,232 coypu records (corresponding to 25,534 grid cells at 5 × 5 km) between 1980 and 2018 from a range of sources and 28 European co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 47 publications
4
25
0
Order By: Relevance
“…In Europe, two semi-aquatic rodents, the coypu ( Myocastor coypus ) and muskrat ( Ondatra zibethicus ), have been included in the list of Invasive Alien Species of Union Concern (EU Regulation No 1143/2014). These two aquatic invasive alien rodents (AIAR) are widespread in Europe [ 19 – 21 ] and have been found across many wetlands in France [ 22 , 23 ]. On top of this, they are important carriers of diseases contagious to humans, including leptospirosis [ 24 ], toxoplasmosis [ 25 ] and alveolar echinococcosis [ 26 ], and livestock and pets, including leptospirosis, giant liver fluke and salmonellosis [ 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, two semi-aquatic rodents, the coypu ( Myocastor coypus ) and muskrat ( Ondatra zibethicus ), have been included in the list of Invasive Alien Species of Union Concern (EU Regulation No 1143/2014). These two aquatic invasive alien rodents (AIAR) are widespread in Europe [ 19 – 21 ] and have been found across many wetlands in France [ 22 , 23 ]. On top of this, they are important carriers of diseases contagious to humans, including leptospirosis [ 24 ], toxoplasmosis [ 25 ] and alveolar echinococcosis [ 26 ], and livestock and pets, including leptospirosis, giant liver fluke and salmonellosis [ 24 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, our database only contains observed costs for cnidarians in Israel, despite the presence of a number of invasive species of jellyfish all over the Mediterranean (Brotz and Pauly 2012). Furthermore, previous findings (Capinha et al 2014;Essl et al 2015;Schertler et al 2020;Zhang et al 2020) have shown that large areas of the Mediterranean basin are predicted to be currently climatically suitable for some of the IAS presenting observed damage costs in other regions. Assuming the presence of suitable dispersal vectors, costs are likely already occurring in these regions (but have not been reported or captured in our database) or likely to occur in additional countries as IAS distributions expand.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, we combined worldwide coypu occurrences (from its native and introduced range) with six bioclimatic predictors to construct ensemble models and predict the suitability of our study region, using the biomod2 framework (see Figures S1-S3 in Supplementary Material 2). For Northern and Southern America, we downloaded GBIF and iNaturalist occurrences, and for Europe we combined the dataset of Schertler et al (2020) with recently published occurrences from both platforms. Only point occurrences with a coordinate uncertainty of less than 10 km were considered for modelling (if this information was missing, we assumed the uncertainty to be lower than our threshold).…”
Section: Methodsmentioning
confidence: 99%
“…Despite its widespread distribution and invasive potential, studies mostly focused on Europe and Northern America (e.g. Hilts et al 2019;Schertler et al 2020). Already two decades ago, Carter and Leonard (2002) pointed out that a comprehensive review on the coypu was not available for Africa and that information for Asian countries was often anecdotal and/or outdated, leading to an unknown status for many countries of introduction in those continents.…”
Section: Introductionmentioning
confidence: 99%